2019
DOI: 10.1111/cdev.13226
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Vocabulary Predicts Nonverbal Executive Function: A 2‐year Longitudinal Study of Deaf and Hearing Children

Abstract: Numerous studies suggest an association between language and executive function (EF), but evidence of a developmental relationship remains inconclusive. Data were collected from 75 deaf/hard‐of‐hearing (DHH) children and 82 hearing age‐matched controls. Children were 6–11 years old at first time of testing and completed a battery of nonverbal EF tasks and a test of expressive vocabulary. These tasks were completed again 2 years later. Both groups improved their scores on all tasks over this period. DHH childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 69 publications
(98 reference statements)
4
57
1
8
Order By: Relevance
“…A negative influence of poorer overall language ability [49], as well as of productive vocabulary [50,51] has been found in other studies. The results from the studies of Botting et al [50] and Jones et al [51] suggest that weaker productive vocabulary skills have a negative influence on non-verbal executive function development. The results from the current study suggest that receptive grammar might influence non-verbal analogical reasoning.…”
Section: Discussionsupporting
confidence: 66%
“…A negative influence of poorer overall language ability [49], as well as of productive vocabulary [50,51] has been found in other studies. The results from the studies of Botting et al [50] and Jones et al [51] suggest that weaker productive vocabulary skills have a negative influence on non-verbal executive function development. The results from the current study suggest that receptive grammar might influence non-verbal analogical reasoning.…”
Section: Discussionsupporting
confidence: 66%
“…In a similar vein, as noted earlier, both Botting et al (2017) and Jones et al (2019) reported evidence to suggest that language ability predicts executive function in children with hearing loss, but executive function does not, in turn, predict language outcomes. Botting et al (2017) conducted a mediation analysis using concurrent measures of language and executive function, and showed that language ability mediated differences in executive function between groups of deaf and hearing children.…”
Section: Introductionsupporting
confidence: 67%
“…The current research aimed to shed light on this unresolved issue. In doing so, the intention was not to evaluate the reciprocal view, that early language impacts later cognitive ability, because that view has not been cast into doubt on the basis of recent research (e.g., Botting et al, 2017; Jones et al, 2019). On the other hand, neither Botting et al (2017) nor Jones et al (2019) found evidence for an influence of cognitive ability on language outcomes, an important finding that warrants further attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations